2017
DOI: 10.1210/en.2017-03065
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9‒Mediated Tspo Gene Mutations Lead to Reduced Mitochondrial Membrane Potential and Steroid Formation in MA-10 Mouse Tumor Leydig Cells

Abstract: The outer mitochondrial membrane translocator protein (TSPO) binds cholesterol with high affinity and is involved in mediating its delivery into mitochondria, the rate-limiting step in hormone-induced steroidogenesis. Specific ligand binding to TSPO has been shown to initiate steroid formation. However, recent studies of the genetic deletion of Tspo have provided conflicting results. Here, we address and extend previous studies by examining the effects of Tspo-specific mutations on steroid formation in hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 75 publications
3
53
0
Order By: Relevance
“…Down‐regulation of CypD prevents MPTP opening and protects against the loss of ΔΨm . Conversely, the loss function of TSPO causes MPTP opening and leads to a reduced ΔΨm . Our results showed that both CypD and TSPO could be poly‐ADP‐ribosylated, but the effects of this modification on the functions of CypD and TSPO were not studied.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Down‐regulation of CypD prevents MPTP opening and protects against the loss of ΔΨm . Conversely, the loss function of TSPO causes MPTP opening and leads to a reduced ΔΨm . Our results showed that both CypD and TSPO could be poly‐ADP‐ribosylated, but the effects of this modification on the functions of CypD and TSPO were not studied.…”
Section: Discussionmentioning
confidence: 67%
“…35 Conversely, the loss function of TSPO causes MPTP opening and leads to a reduced ΔΨm. 21,36 Our results showed that both CypD and TSPO could be poly-ADP-ribosylated, but the effects of this modification on the functions of CypD and TSPO were not studied. As reported, poly-ADP-ribosylation can serve as a marker for ubiquitinproteasomal system (UPS)-dependent protein degradation.…”
Section: Mitophagy Inhibition Due To Knockdown Ofmentioning
confidence: 84%
“…These factors were not considered in the study by Selvaraj’s group . Moreover, we recently generated Tspo KO MA‐10 cell lines via CRISPR/Cas9 technology and observed that these cells make little to no steroids and that PK 11195 stimulation did not affect steroid biosynthesis in the TSPO‐deficient cells …”
Section: Genetic Deletion Of Tspo In Cell Modelsmentioning
confidence: 99%
“…[18][19][20][21] Moreover, we recently generated Tspo KO MA-10 cell lines via CRISPR/Cas9 technology and observed that these cells make little to no steroids and that PK 11195 stimulation did not affect steroid biosynthesis in the TSPO-deficient cells. 62 One of the main arguments used by Selvaraj and colleagues is that TSPO plays no role in steroidogenesis and the adrenal tumour H295R cells do not contain TSPO but produce steroids. 63 Indeed, this observation is cited as the "gold standard" to debunk the role of TSPO in steroid biosynthesis.…”
Section: Genetic Deletion Of Tspo In Cell Modelsmentioning
confidence: 99%
“…22 Consistent with this, knockout of Tspo in MA-10 cells by CRISPR/Cas9 technology resulted in little to no steroid (progesterone) production. 23 In vivo, rodents in which Tspo was knocked out did not produce corticosterone in response to adrenocorticotropic hormone (ACTH), 24 and had reduced total steroidogenic output and age-dependent androgen deficiency. 25 Additionally, the stimulation of TSPO by several TSPO-specific drug ligands was shown to increase steroid formation in MA-10 cells and primary Leydig cells in vitro, and in Leydig cells in vivo.…”
Section: Introductionmentioning
confidence: 99%